2020
DOI: 10.3389/fpsyg.2020.00502
|View full text |Cite
|
Sign up to set email alerts
|

Facial Emotion Recognition and Executive Functions in Insomnia Disorder: An Exploratory Study

Abstract: Background: Clinical and experimental findings suggest that insomnia is associated with changes in emotional processing and impairments in cognitive functioning. In the present study, we investigate the relationship between facial emotion recognition and executive functioning among individuals with insomnia as well as healthy controls. Method: A total of 11 individuals (mean age 31.3 ± 9.4) diagnosed with insomnia disorder and 15 control participants (mean age 24.8 ± 4.6) took part in the study. Participants r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…In addition, we showed that social communication, which was enhanced by the treatment, was significantly associated with emotion recognition, an essential skill for social interaction that previous studies have shown is deficient in individuals with ASD [4,60]. Notably, CF is associated with emotional recognition in healthy children [61] as well as in people with ASD [17], as emotion recognition has been shown to require flexible reasoning strategies in response to a situation [62]. In other words, our results may imply that tDCS with left dlPFC cathode placement and right supraorbital region anode placement and concurrent "cold" EF cognitive remediation training may promote flexible problem solving.…”
Section: Clinical and Cognitive Effects Of Prefrontal Tdcs With Concu...mentioning
confidence: 68%
“…In addition, we showed that social communication, which was enhanced by the treatment, was significantly associated with emotion recognition, an essential skill for social interaction that previous studies have shown is deficient in individuals with ASD [4,60]. Notably, CF is associated with emotional recognition in healthy children [61] as well as in people with ASD [17], as emotion recognition has been shown to require flexible reasoning strategies in response to a situation [62]. In other words, our results may imply that tDCS with left dlPFC cathode placement and right supraorbital region anode placement and concurrent "cold" EF cognitive remediation training may promote flexible problem solving.…”
Section: Clinical and Cognitive Effects Of Prefrontal Tdcs With Concu...mentioning
confidence: 68%
“…Numerous studies have confirmed that sleep loss alters normal affective processing and biased perception, memory, and emotions toward negative aspects of experience. For example, de Almondes et al reported dysfunction of executive function and facial emotion recognition of negative emotions (fear and sadness) in patients with insomnia ( 26 ). Kyle et al found that patients with insomnia had a significantly lower ability to identify the emotional intensity of sadness and fearful expressions than good sleepers ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies testing more categories of basic emotions (e.g., anger, fear and surprise) and complex emotions (e.g., shame, guilt and pride) may provide more comprehensive insights into the emotion recognition performance of children with SDB. The current investigation only used the static expressions, however, the processing of dynamic expressions might be different from that of static emotions, as previous research indicated [ 58 ]. It would be interesting to explore the recognition performance of dynamic emotions in the future.…”
Section: Discussionmentioning
confidence: 99%